A rare cause of monogenic cerebral small vessel disease and stroke: Cathepsin A-related arteriopathy with strokes and leukoencephalopathy (CARASAL) - Budhdeo, Sanjay; de Paiva, Anderson Rodrigues Brandão; Wade, Charles; Lopes, Laura Cardia Gomes [UNESP]; Della-Ripa, Bruno; Davagnanam, Indran; Lucato, Leandro; Mummery, Catherine J.; Kok, Fernando; Houlden, Henry; Werring, David J.; Lynch, David S. (Springer Nature, 2022)
Background: Cathepsin A-related arteriopathy with strokes and leukoencephalopathy (CARASAL) is a rare monogenic cause of cerebral small vessel disease. To date, fewer than 15 patients with CARASAL have been described, all of common European ancestry. Methods: Clinical and imaging phenotypes of two patients are presented. Genetic variants were identified using targeted Sanger and focused exome sequencing, respectively. Results: Both patients carried the same pathogenic p.Arg325Cys mutation in CTSA. One patient of Chinese ethnicity presented with migraine, tinnitus and slowly progressive cognitive impairment with significant cerebral small vessel disease in the absence of typical cardiovascular risk factors. She later suffered an ischaemic stroke. A second patient from Brazil, of Italian ethnicity developed progressive dysphagia and dysarthria in his 50s, he later developed hearing loss and chronic disequilibrium. Magnetic resonance imaging in both cases demonstrated extensive signal change in the deep cerebral white matter, anterior temporal lobes, thalami, internal and external capsules and brainstem. Conclusions: CARASAL should be considered in patients with early onset or severe cerebral small vessel disease, particularly where there are prominent symptoms or signs related to brainstem involvement, such as hearing dysfunction, tinnitus or dysphagia or where there is significant thalamic and brainstem involvement on imaging.
Keywords: CARASAL; Genetics; Leukoencephalopathy; Small vessel disease; Stroke